Application of Total Productive Maintenance and Overall Equipment Effectiveness in Improving Ampoule Filling Machine Performance: A Case Study in a Pharmaceutical Manufacturing - Rohmah, Mufidah Erngganis Devia; Noya, Sunday; Putrianto, Novenda Kartika (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2025)
This study aims to improve the effectiveness of ampoule filling machines in a pharmaceutical manufacturing company through the implementation of Total Productive Maintenance (TPM) supported by Overall Equipment Effectiveness (OEE) evaluation. The study was motivated by a decline in machine performance during the period from January to August 2024, characterized by low production output, high downtime, and high defect rates. A quantitative research approach was employed using primary and secondary data collected from 30 production batches through field observations, interviews, and documentation review. Machine effectiveness was evaluated using OEE, which consists of availability, performance, and quality components, while efficiency losses were identified using the Six Big Lossesframework. Root causes were analyzed using a Fishbone diagram, and improvement actions were formulated based on relevant TPM pillars. The results show that the initial average OEE value was 56%, significantly below the world-class benchmark of 85%, with breakdown losses and quality defect losses identified as the dominant contributors to inefficiency. After implementing TPM-based improvements—specifically the replacement and recalibration of malfunctioning swing conveyor sensors and the redesign of the ampoule outfeed system—the average OEE value increased to 71.9%. Improvements were also observed in the OEE components, with availability increasing to 86.5%, performance to 92.0%, and quality to 90.5%. These results indicate a substantial reduction in downtime and defect rates. The study confirms that the integration of TPM and OEE is effective in enhancing machine effectiveness and production efficiency in sterile pharmaceutical manufacturing.